Anaerobic Metabolism Markers as a Guide of Resuscitation Effort and Mortality Benefit in Septic Shock Among Egyptian Population - Walid Mohamed Kamel Ahmed; Ramy Mohamed El Sayed Ibrahim Kishk; Dalia Mohamed Ragab; Mohamed Ibrahim Desouky (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Venous-to-arterial carbon dioxide pressure and ratio of carbon dioxide gap divided by difference in arterial-venous oxygen content might be relevant in septic shock management. The aim of this study was to evaluate whether carbon dioxide gap and ratio of carbon dioxide gap divided by difference in oxygen content following septic shock resuscitation could predict mortality. Methods Fifty septic shock patients were included in this study. Arterial and central venous blood gas samples were measured before and 6 hours following fluid resuscitation and vasopressors. Results Our study population was 61.6±7.4 years (31 males). Thirty-three patients survived. Paired comparisons in nonsurvivors showed worsening hemodynamics, carbon dioxide gap, ratio of carbon dioxide gap divided by difference in oxygen content, and lactate clearance. Mortality prediction cutoffs for lactate (40 mg/dl) with sensitivity (88.2%) and specificity (78.8%), carbon dioxide gap (6 mmHg) with sensitivity (94.1%) and specificity (63.6%) and ratio of carbon dioxide gap divided by difference in oxygen content (1.6) with sensitivity (88.2%) and specificity (60.6%). Combined lactate and the ratio of carbon dioxide gap divided by difference in oxygen content had sensitivity of 88.2% and specificity of 93.9%. Combined lactate and carbon dioxide gap had sensitivity of 82.4% and specificity of 90.9%. Discussion Changes in carbon dioxide gap and ratio of carbon dioxide gap divided by difference in arterial-venous oxygen content during resuscitation of septic shock were related to in-hospital mortality. Adding carbon dioxide gap and the ratio of carbon dioxide gap divided by difference in arterial-venous oxygen content to lactate increased the accuracy of mortality prediction.